Stratospheric Trailing Gravity Waves from New Zealand - Jiang, Qingfang; Doyle, James D.; Eckermann, Stephen D.; Williams, Bifford P. (Journal of the atmospheric sciences, 2019)
Gravity waves are frequently observed in the stratosphere, trailing long distances from mid- to high-latitude topography. Two such trailing-wave events documented over New Zealand are examined using observations, numerical simulations, and ray-tracing analysis to explore and document stratospheric trailing-wave characteristics and formation mechanisms. We find that the trailing waves over New Zealand are orographically generated and regulated by several processes, including interaction between terrain and mountaintop winds, critical-level absorption, and lateral wave refraction. Among these, the interaction between topography and low-level winds determines the perturbation energy distribution over horizontal scales and directions near the wave source, and accordingly, trailing waves are sensitive to terrain features and low-level winds. Terrain-forced wave modes are filtered by absorption associated with directional wind shear and Jones critical levels. The former plays a role in defining wave-beam orientation, and the latter sets an upper limit for the permissible horizontal wavelength of trailing waves. On propagating into the stratosphere, these orographic gravity waves are subject to horizontal refraction associated with the meridional shear in the stratospheric westerlies, which tends to elongate the wave beams pointing toward stronger westerlies and shorten the wave beams on the opposite side.